Secondary metabolites from Colletotrichum capsici, an endophytic fungus derived from Siegesbeckia pubescens Makino. Issue 16 (18th August 2017) - Wang, Fuqian; Ma, Haoran; Hu, Zhengxi; Jiang, Jie; Zhu, Hucheng; Cheng, Lu; Yang, Quanwei; Zhang, Hong; Zhang, Geng; Zhang, Yonghui
Abstract: A rare new tremulane sesquiterpenoid analogue, 11, 12-epoxy-5, 6- seco -1, 6(13)-tremuladien-5, 12-olide (1 ), together with five known altenuene derivatives (2 –6 ) was isolated from the cultures of Colletotrichum capsici, which was isolated as an endophytic fungus from fresh leaves of Siegesbeckia pubescens Makino (Compositae). Their structures were elucidated by means of spectroscopic methods and comparison with literature data. All compounds isolated were reported for the first time from the fungus C. capsici . Abstract :